Accessibility of and barriers to the use of eye health services in Kumasi Metropolis, Ghana - Eunice A. Frempong; Diane W. Van Staden (AOSIS, 2024)
Background: There is a high prevalence of vision impairment and blindness in Africa. The poor access to eye health services, among other barriers, has been found to have a considerable effect on the burden of avoidable vision loss and blindness, particularly in low- and middle-income countries. Aim: To determine the accessibility of and barriers to the utilisation of eye health services in the Kumasi Metropolis of Ghana. Setting: A descriptive cross-sectional survey was conducted in the Kumasi Metropolis of the Ashanti Region in Ghana to identify barriers affecting the utilisation of eye health services. Methods: Convenience sampling was used to recruit participants visiting the eye clinics at five selected District Municipal Hospitals for the first time. Data were collected by means of questionnaires and analysed using Statistical Package for Social Sciences (SPSS). Results: Barriers faced by participants when accessing eye health services included distance to the clinic, cost of services, time spent away from work and/or school, self-medication and long waiting periods. Conclusion: The study found that eye care services in the Kumasi Metropolis, Ghana are largely accessible, but underutilised. Improvement of public health education initiatives through engagement with community groups will also enhance uptake at health care facilities. Contribution: Underutilisation of health services in the Metropolis has been identified in the study and must be addressed by health managers in various sectors. Accessibility is relatively good but can further be improved especially for the elderly to be able to utilise health care services with ease.